ANALISIS UNSUR INTRINSIK PUISI DALAM BUKU ANTOLOGI CERPEN DAN PUISI ANAK BALON KEINGINAN PENYUSUN KORRIE LAYUN RAMPAN DAN IMPLIKASI PEMBELAJARAN DI SD - Ilhami, Dina Rainida; Gunawan, Dani; Nuriyanti, Risma (IPI Press, 2021)
Learning children's literature is an important part of the Indonesian language curriculum at elementary school level, aimed at developing appreciation for literary works and understanding everyday life through poetry. This research aims to analyze the intrinsic elements of children's poetry in the Anthology of Short Stories and Children's Poetry